Pengaruh Likuiditas, Leverage, Rasio Aktivitas, dan Good Corporate Governance Terhadap Financial Distress Perusahaan Industri dan Bahan Kimia pada Indeks Saham Syariah Indonesia - Trisno Wahyudi Illahi; Aidil Novia; Sandra Ayu; Defriko Gusma Putra (Universitas Negeri Padang, 2025)
This research aims to examine how Liquidity, Leverage, Activity Ratio, and Good Corporate Governance Influence Financial Distress among basic industrial and chemical companies listed on the Indonesian Sharia Stock Index (ISSI) during the 2020–2024 period. Financial distress refers to a severe financial condition in which a company faces difficulties in fulfilling its obligations, including the payment of debts, interest, and operational costs. In this study, financial distress is assessed using the Springate model, where a score below 0.862 indicates that a company is experiencing distress. The study adopts a quantitative method and relies on secondary data. From a total population of 67 companies, 54 firms were selected as the final sample after the outlier screening process. The sampling method applied is purposive sampling, and the data are analyzed using panel data regression with EViews 12 software. The findings reveal that liquidity has a negative and statistically significant impact on financial distress, while leverage shows a positive and significant effect. The activity ratio is found to have a negative and significant influence, whereas Good Corporate Governance demonstrates a positive but statistically insignificant effect. Simultaneously, all four independent variables significantly affect financial distress. These results highlight the crucial role of maintaining adequate liquidity, managing debt levels, improving operational efficiency, and strengthening corporate governance practices to reduce the risk of financial distress